Otimização de protocolos de expressão e purificação de metiltransferases de ZIKV e YFV - Dantas, Letícia Piazentin (Universidade Federal de São Carlos, 2025)
This study aimed to optimize protocols for the expression and purification of methyltransferases from Zika (ZIKV) and Yellow Fever (YFV) viruses, which belong to the Flavivirus genus, which includes important pathogens associated with epidemic outbreaks and serious complications, such as microcephaly, Guillain-Barré syndrome and hemorrhagic hepatitis. These viruses have RNA genomes with a 5' cap modified by methyltransferases (MTase), ensuring greater stability and evasion of the host's immune system. To explore these proteins as potential therapeutic targets, expression tests were performed in Escherichia coli Rosetta DE3, identifying the ideal conditions as plasmid M11, ZYM 5052 medium and a temperature of 18°C for methyltransferase from the virus that causes Yellow Fever and for methyltransferase from the virus that causes Zika Fever. YFV methyltransferase purification was performed by affinity and molecular exclusion chromatography, resulting in proteins of high purity and stability in HEPES (NaOH) buffer (pH 7.5, 500 mM NaCl and 5% glycerol), which is ideal for functional preservation of the protein. However, Zika virus methyltransferase showed lower efficiency in the purification process, which negatively impacted its stability and final yield.This study provides a solid basis for expression and purification of methyltransferases for futurebiochemical and structural investigations, in addition to contributing to the advancement in thedevelopment of antiviral strategies against these flaviviruses. The next work steps include the optimization of the ZIKV methyltransferase purification protocol, biophysical, biochemical and structural characterization of the methyltransferases, using techniques such as size exclusion chromatography (SEC) with multiangle light scattering (MALS) (SEC-MALS), differential scanning fluorimetry (DSF), circular dichroism (CD), fluorescence spectroscopy and X-ray crystallography, in addition to functional analysis of enzymatic activity.
Optimization of expression and purification protocols for ZIKV and YFV methyltransferases
Keywords: Flavivírus; Metiltransferase; Expressão; Purificação; CIENCIAS BIOLOGICAS::BIOQUIMICA